KECERDASAN BUATAN UNTUK MATA KECIL: TINJAUAN SISTEMATIS TERHADAP DEEP LEARNING DALAM MENGEVALUASI KATARAK PEDIATRIK - Tjoeng, Eric; Annisa, Nur Devina (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Background: Pediatric or congenital cataract (CC) is a leading cause of visual impairment and blindness in children worldwide. Deep learning (DL), a subfield of artificial intelligence, has the potential to enhance diagnosis, treatment, and outcomes in various medical fields. Research Objectives: summarize and evaluate the diagnostic and prediction capabilities of DL algorithms for CC. Methods: From 1st February to 25th March 2023, a literature search was conducted in databases such as PubMed, ScienceDirect, EMBASE, and EBSCO, as well as alternative sources such as Google Scholar. Search terms included “pediatric/congenital cataract”, “artificial intelligence